2018
DOI: 10.1136/bmjopen-2018-025411
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the Namaste Care Family programme on quality of life of nursing home residents with advanced dementia and on family caregiving experiences: study protocol of a cluster-randomised controlled trial

Abstract: IntroductionQuality of life of people with advanced dementia living in nursing homes is often suboptimal. Family caregivers can feel frustrated with limited contact with their relatives, which results in visits that are perceived as stressful and not very meaningful. Few psychosocial interventions are specifically developed for people with advanced dementia, and actively involve family caregivers or volunteers. Also, interventions usually stop when it becomes difficult for people to participate. The Namaste Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 88 publications
(80 reference statements)
0
37
0
Order By: Relevance
“…Learning from other ongoing international studies in this area could inform recommendations. 31 In terms of implementation processes, the resources created for the intervention delivery were well received, but not greatly referred to following the initial training. Further review of the materials, including the guide, would be undertaken prior to a full trial (see below) at which time consideration of family and volunteer roles could be addressed.…”
Section: Intervention Content and Implementationmentioning
confidence: 99%
“…Learning from other ongoing international studies in this area could inform recommendations. 31 In terms of implementation processes, the resources created for the intervention delivery were well received, but not greatly referred to following the initial training. Further review of the materials, including the guide, would be undertaken prior to a full trial (see below) at which time consideration of family and volunteer roles could be addressed.…”
Section: Intervention Content and Implementationmentioning
confidence: 99%
“…NC can improve communication and the relationships families and friends have with the person with dementia 18. NC is a psychosocial intervention that has been implemented variably internationally;18 research is beginning to develop understanding about the intervention and it’s cost implications,19–25 but to our knowledge has only been formally evaluated in care home settings. A hospice in the North East of England has made provisions to provide NC in the person’s own home.…”
Section: Introductionmentioning
confidence: 99%
“…The committee declared that no further formal review was needed, since the study was declared exempt from the scope of the Medical Research Involving Human Subjects Act. Detailed information on the study design and the Namaste Care Family program trial is provided elsewhere [17]. Funding sources were not involved in the design and execution of the study or writing of the study results.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the nature of the intervention, the group allocation could not be masked. Sample size calculations indicated that with 192 participants, power sufficed to detect a relevant difference in participants' quality of life [17].…”
Section: Randomization and Sample Sizementioning
confidence: 99%